Economy and Trade: Structural Reform Progress Index in Central America and Panama During the Nineties - Muñoz, Erlend (2007)
This document looks for the quantification of the advancement of the process of structural reform in Costa Rica, Honduras, El Salvador, Guatemala, Nicaragua and Panama, in five areas: commercial, tributary policy, political finance, relative reduction of the size of the State and labor legislation. The period under study is the nineties (1990-2000). The investigation calculates and analyzes a quantitative index of the reform in the structural policies of the countries of the Central American Isthmus for the period 1990-2000, in the five aforementioned areas. By the construction of the index, the comparison of the level of reform reached during the period between the involved countries becomes possible and, in addition, it allows to compare the degree of reform in the structural policies in the five areas within the same country. The information shows that the reform process has not advanced at the same rate in the countries of the isthmus, and even the advancement has not been uniform between the countries; that is to say, during the period it is possible to find years during which the reform process undergoes backward movements.